2018
DOI: 10.1126/scisignal.aaq1060
|View full text |Cite
|
Sign up to set email alerts
|

KIF22 coordinates CAR and EGFR dynamics to promote cancer cell proliferation

Abstract: The Coxsackie and Adenovirus Receptor (CAR) is a transmembrane receptor that plays a key role in cell-cell adhesion. CAR is found in normal epithelial cells and is increased in abundance in various human tumors, including lung carcinomas. Here, we investigated the potential mechanisms by which CAR contributes to cancer cell growth and found that depletion of CAR in human lung cancer cells reduced anchorage-independent growth, epidermal growth factor (EGF)–dependent proliferation, and tumor growth in vivo. EGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…In this issue of Science Signaling, Roth et al (11) and Pike et al (12) from the Yarden and Parsons groups, respectively, used different proteomic approaches to uncover new insight into the complex question of how EGF-induced signaling modulates cytoskeletal remodeling during cell migration, adhesion, and division. Roth et al used stable isotope labeling by amino acids in cell culture (SILAC)-based phosphoproteomic analysis to identify previously unknown proteins involved in growth factorinduced migration in mammary epithelial cells (11).…”
mentioning
confidence: 99%
“…In this issue of Science Signaling, Roth et al (11) and Pike et al (12) from the Yarden and Parsons groups, respectively, used different proteomic approaches to uncover new insight into the complex question of how EGF-induced signaling modulates cytoskeletal remodeling during cell migration, adhesion, and division. Roth et al used stable isotope labeling by amino acids in cell culture (SILAC)-based phosphoproteomic analysis to identify previously unknown proteins involved in growth factorinduced migration in mammary epithelial cells (11).…”
mentioning
confidence: 99%
“…KIF22 bound to microtubules which were important in receptor traffic, including EGFR [42,43]. KIF22 regulated microtubule stability and upregulated EGFR signaling which promoted CAR phosphorylation and relocalization at plasma membrane to increase cell division [44].…”
Section: Discussionmentioning
confidence: 99%
“…Both KIF3 and KIF4 have been identified as tumor suppressor genes in gastric cancer . Pike et al demonstrated that chromokinesin KIF22 was coordinated with coxsackievirus and adenovirus receptor (CAR) and EGFR, two key plasma membrane receptors that facilitate cancer cell division, resulting in the promotion of CAR and EGFR dependent tumorigenesis in lung cancer . Hung et al proposed that KIF14 might regulate the recruitment of the adhesive molecule cadherin 11 to the cell membrane in LUAD cell lines …”
Section: Discussionmentioning
confidence: 99%
“…18,19 Pike et al demonstrated that chromokinesin KIF22 was coordinated with coxsackievirus and adenovirus receptor (CAR) and EGFR, two key plasma membrane receptors that facilitate cancer cell division, resulting in the promotion of CAR and EGFR dependent tumorigenesis in lung cancer. 20 Hung et al proposed that KIF14 might regulate the recruitment of the adhesive molecule cadherin 11 to the cell membrane in LUAD cell lines. 21 KIF18A, an important member of KIF8 family, plays key roles in the regulation of chromosome congression during prometaphase and in the maintenance of chromosome alignment during metaphase.…”
Section: Discussionmentioning
confidence: 99%